Prinsip Dakwah Dalam Pandangan Fethullah Gulen - Kholid Noviyanto (Faculty of Ushuluddin and Dakwah, UIN K.H. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2021)
Islam is a religion that teaches about unity. because of unity is expected people to be able to know each other from a variety of community backgrounds both tribes. customs. and others. Da'i is a title given by a person who is entrusted to promote Islam and restore awareness of unity to the community through the principle of da'wah. This is an insight da'i in carrying out duties as a preacher. This study reveals the principle of da'wah in the view of Fethullah Gulen by using a qualitative type of research with literature studies and analyzed using qualitative content analysis. The results of related research show that Fethullah Gulen in his da'wah uses the principle of always maintaining the unity of the people and applying the ethics of da'wah which includes friendly attitudes. upholding tolerance. and openness of opinion through dialogue between people and culture.